RECONCEPTUALIZING ENGLISH EDUCATION OF FILIPINO ESL LEARNERS FROM PUBLIC SECONDARY LEARNING INSTITUTIONS IN THE PHILIPPINES - Orlyn Joyce Dollente Esquivel (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
This study examined the results of a survey questionnaire on 300 Grade 10 Filipino ESL (English as a second language) learners, randomly selected from two public secondary learning institutions in the Philippines. The survey was used to investigate the students’ attitudes toward the English language and their own learning experiences. For the data collection, the survey questionnaire consists of 20 statements, in which every five statements belong to one particular category of the four English skills (listening, speaking, reading, and writing skills). Overall findings of the descriptive-quantitative analyses unveiled that most of the students elicited a high degree of negative attitudes toward the English language. This paper concludes with educational implications to help develop ‘positive attitudes’ in English language learning which are not only limited to Filipino ESL students, but also to other ESL learners around the world.